2020
DOI: 10.1080/09613218.2020.1789444
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the dynamics of China’s prefabricated building policies from 1956 to 2019: a bibliometric analysis

Abstract: Compared to buildings constructed in situ, prefabricated buildings (PBs) offer many environmental benefits in terms of carbon emissions, energy consumption, material consumption, and waste generation. To mitigate adverse impacts by the building sector on the environment, PBs have been widely applied in many countries. Although PB policies (PBPs) have played a significant role in guiding, supporting, and promulgating China's PB development, few studies have systematically investigated these PBPs. As a result, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 56 publications
1
50
1
Order By: Relevance
“…In the “Green Building and Green Ecological Urban Development Planning” (hereinafter referred to as the “Planning”), MOHURD [ 64 ] proposed six suggestions to accelerate the development of the GB industry during the 12th Five-Year Plan period, including the use of prefabrication technology. In conclusion, similar to the study of Wang et al [ 31 ], a strong linkage between “green building” and “prefabrication technology” appeared in stage 3. In addition, in the “Planning,” MOHURD [ 64 ] proposed to formulate green building evaluation standards suitable for different climate regions and building types during the 12th Five-Year Plan period.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…In the “Green Building and Green Ecological Urban Development Planning” (hereinafter referred to as the “Planning”), MOHURD [ 64 ] proposed six suggestions to accelerate the development of the GB industry during the 12th Five-Year Plan period, including the use of prefabrication technology. In conclusion, similar to the study of Wang et al [ 31 ], a strong linkage between “green building” and “prefabrication technology” appeared in stage 3. In addition, in the “Planning,” MOHURD [ 64 ] proposed to formulate green building evaluation standards suitable for different climate regions and building types during the 12th Five-Year Plan period.…”
Section: Resultssupporting
confidence: 87%
“…A review of the GBPs issued from 1986 to 2019 showed that a total of 14 agencies participated, as shown in Table 1 . Since the names of some government agencies have changed in the past 34 years, to avoid confusion, similar to the study by Wang et al [ 31 ], this paper adopted the latest names of these agencies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, co-word analysis is applied to map the topics of science and technology policies via manually labeling topics of each policy document and selecting high-frequency keywords ( Huang et al, 2015 ). It was also used to visualize the interactions among different keywords from 136 prefabricated buildings policies to describe prefabricated buildings policy system over time ( Wang et al, 2020 ). Zhou et al (2020) explored the characteristics of policy evolution of China's new energy vehicles industry using co-word analysis based on 154 policy documents from Chinese central government.…”
Section: Related Workmentioning
confidence: 99%